Regresi Data Panel dengan Kesalahan Standar Driscoll-Kraay: Analisis Kejahatan dan Indikator Sosial Ekonomi di Sumatera Barat (2017–2024) - Andini Diva Luthfiyah; Dhio Ervandi; Tessy Octavia Mukhti (Departemen Statistika Universitas Negeri Padang, 2026)
Criminal behavior is a complex social issue that threatens public safety and hinders regional development. In Indonesia, the crime rate varies across provinces and is influenced by multiple socioeconomic and structural factors. In West Sumatra Province, fluctuations in crime risk over time highlight the need for a deeper analysis of its determining factors. Understanding these factors is essential for the government to formulate effective and targeted crime prevention policies. This study aims to analyze the determinants of crime risk in West Sumatra Province using panel data from 2017 to 2024, covering 19 districts and cities, allowing for a more robust and comprehensive evaluation of both temporal and cross-sectional variations. The variables examined include the open unemployment rate, poverty rate, percentage of youth not in employment, education, or training (NEET), and the COVID-19 pandemic as a dummy variable. Panel data regression analysis was employed, and the results indicate that the most appropriate model is the Random Effects Model (REM). The findings show that the open unemployment rate and the pandemic variable have a significant effect on crime risk at the 5% significance level, while the poverty rate is significant at the 10% level. These results provide valuable insights for policymakers in addressing the root causes of crime in West Sumatra through employment generation, poverty alleviation, and preparedness for crisis situations.